Linguopragmatic and Cognitive Features of the Emotional Layer in Gender Linguistics (on the Example of the English and Uzbek Languages) - Haqberdiyeva Gulrukh Tolibovna (Goodwood Publishing, 2026)
Purpose: This study explores how emotions are expressed, perceived, and conceptualized by male and female speakers in English and Uzbek discourse, focusing on the linguistic and cognitive aspects of emotional language across cultures. Research Methodology: The study analyzed 240 discourse samples, equally divided by language (English and Uzbek) and gender, using methods from gender linguistics, pragmatics, and cognitive linguistics. Results: Female speakers used more intensifiers, hedges, and empathy-oriented expressions, reflecting relational communication, while male speakers used fewer emotional amplifications and favored metaphorical expressions based on force and heat. The study also identified universal emotional metaphors and culturally specific ones in Uzbek, particularly heart-centered models influenced by collectivist values. Conclusions: The study concluded that emotional language is socially constructed and cognitively grounded, playing a key role in gender identity performance, with both cultural and gender differences shaping emotional expression. Limitations: The study focused on English and Uzbek, limiting its applicability to other languages and cultures. The sample size of 240 may also not capture all emotional nuances. Contributions: This research enhances gender and cross-cultural discourse analysis, offering insights into how emotional expressions are influenced by gender and culture. It contributes to fields like linguistics, psychology, and cultural studies.